2021
DOI: 10.1177/10499091211026674
|View full text |Cite
|
Sign up to set email alerts
|

What Surrogates Understand (and Don’t Understand) About Patients’ Wishes After Engaging Advance Care Planning: A Qualitative Analysis

Abstract: Background: The goal of advance care planning (ACP) is to improve end-of-life decision-making for patients and their spokespersons, but multiple studies have failed to show substantial or consistent benefit from ACP. Understanding how and why ACP under-performs in the setting of complex medical decision-making is key to optimizing current, or designing new, ACP interventions. Aim: To explore how ACP did or did not contribute to a spokespersons’ understanding of patient wishes after engaging in ACP. Design: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The point is that we ought not simply equate surrogate decision-making with deciding/acting in a way that is consistent with that patient’s wishes. This, in conjunction with our research findings in Simmons et al 20 and Van Scoy et al 21 regarding the variability in how spokespersons interpret surrogate decision-making, led us to create a process for both exploring and adjudicating what should count as a surrogate decision, and why. In a forthcoming qualitative manuscript, we will detail how spokespersons interpreted surrogate decision-making and how this concept differed from the notion of advocacy.…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations
“…The point is that we ought not simply equate surrogate decision-making with deciding/acting in a way that is consistent with that patient’s wishes. This, in conjunction with our research findings in Simmons et al 20 and Van Scoy et al 21 regarding the variability in how spokespersons interpret surrogate decision-making, led us to create a process for both exploring and adjudicating what should count as a surrogate decision, and why. In a forthcoming qualitative manuscript, we will detail how spokespersons interpreted surrogate decision-making and how this concept differed from the notion of advocacy.…”
Section: Introductionmentioning
confidence: 52%
“…In exploring this with her, she reported that the proposed treatment was really a “no-brainer” because there was “no real choice” in the matter, and therefore it did not constitute a decision at all. So, too, we found in Simmons et al 20 and Van Scoy et al 21 that spokespersons often drew little distinction between serving as an advocate for their loved one (for example, requesting that the doctor send the patient to a rehab facility rather than return home or calling 911 when their loved one was short of breath) vs acting as a surrogate decision-maker . Qualitative analysis provides evidence that family members of patients with severe chronic illness often have quite varied and overlapping perspectives on what advocacy means and how it is related to surrogate decision-making.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Therefore, the challenge is that the surrogate can only speculate about the patient's intentions [29]. I believe that coordinating with the patient and family to discuss ACP early in the treatment initiation phase represents necessary support by healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%